Asosiasi Lama Studi dan IPK pada Mahasiswa Aktif Program Studi Ekonomi Syari’ah FAI-UIKA Bogor Semester Genap 2022/2023 - Hakiem, Hilman; Kartika, Tika; Satria Ramdani, Muhamad (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The aim of this research is to determine the association between length of study and CGPA among active students of the Sharia Economics Study Program, Faculty of Islamic Studies, University of Ibn Khaldun Bogor, even semester 2022/2023. The method used in this research is Chi-Square, namely to determine whether there is an association between the two variables studied, in this case length of study and GPA. It was found that the calculated results X2count < X20.05 (2) (1.1067 < 5.591), then accepted H0, which means that there is no association between length of study and CGPA for active students of the Sharia Economics Study Program, Faculty of Islamic Studies, University of Ibn Khaldun Bogor, even semester 2022/2023.